2018
DOI: 10.1002/jemt.23019
|View full text |Cite
|
Sign up to set email alerts
|

Tubular dentin sealer penetration after different final irrigation protocols: A confocal laser scanning microscopy study

Abstract: The aim of this study was to evaluate tubular dentin sealer penetration, comparing different final irrigation protocols using a conventional needle (CONV), EndoActivator system (EAS), EndoVac system (EVS), and ultrasound (PUI). Initially, fifty-two first maxillary molars with a single canal in the palatal root, without abrupt curvatures, resorptive processes, or previous endodontic treatment were selected for this study. Then, the crowns were sectioned to obtain palatal roots 15 mm in length. The root canals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
17
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 35 publications
3
17
0
3
Order By: Relevance
“…In this study, among the four different irrigation techniques, no significant differences were observed in the investigated parameters in relation to sealer penetration. While these findings align well with some of the earlier studies [7,9], the results of other studies in a review of the literature were found to be contrasting [10,11,13,[33][34][35]. Galler et al [34] found greater penetration depths in the apical thirds for ultrasonic and sonic activation groups compared to MDA.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…In this study, among the four different irrigation techniques, no significant differences were observed in the investigated parameters in relation to sealer penetration. While these findings align well with some of the earlier studies [7,9], the results of other studies in a review of the literature were found to be contrasting [10,11,13,[33][34][35]. Galler et al [34] found greater penetration depths in the apical thirds for ultrasonic and sonic activation groups compared to MDA.…”
supporting
confidence: 87%
“…Several techniques have been used for root canal irrigation, such as conventional needle irrigation (CI), manual dynamic activation (MDA), sonic irrigation (SI), and passive ultrasonic irrigation (PUI). There are numerous studies which investigate the effect of different agitation techniques on the removal of the smear layer and the sealer penetration into dentinal tubules [7][8][9][10][11][12][13]. The mechanical flushing action created by CI is relatively weak [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dentes com rizogênese incompleta são aqueles que ainda não atingiram o estágio 10 de Nolla e, portanto, não apresentam toda a camada de dentina radicular revestida por cemento. As raízes desses dentes apresentam paredes finas e frágeis e abertura apical acentuadamente ampla (Lin et al,2017;da Silva, 2018).…”
Section: Introductionunclassified
“…Paralelamente, o Endovac promove melhor distribuição da solução irrigadora por todo o comprimento de trabalho (Adorno et al, 2015) e o seu emprego permite uma maior penetrabilidade do material obturador na dentina tubular, principalmente no terço apical do canal (Kara Tuncer e Unal, 2014; Machado et al, 2018). Assim, o preparo biomecânico associado ao sistema de irrigação por pressão negativa pode ser considerado um protocolo terapêutico promissor para o combate à infecção do sistema de canais radiculares de dentes com lesão periapical (Hockett et al, 2008; da Cohenca et al, 2013), inclusive nos casos de rizogênese incompleta (Cohenca et al, 2010;Rodríguez-Benítez et al, 2014).…”
Section: Introductionunclassified